2022
DOI: 10.3390/toxics10110641
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Toxic Effects of Heavy Metals on Waterbirds and Their Prey Species in Freshwater Habitats

Abstract: Waterbirds may be a good indicator of harmful metal levels in aquatic environments. Waterbirds’ organs and tissues were tested for the presence of pollutants, such as metals. However, very few reports describe the use of bird feathers and their prey in metal analysis. In the present research, seven metals were measured in the tissue, kidney, liver, and feathers of the Indian pond heron, the black-crowned night heron, and their prey species, including crabs, prawns, molluscs, and fishes from a freshwater lake. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Interestingly, there is no discernible difference in all the metal accumulations in the feathers among the six groups of birds, but the maximum concentrations of the heavy metals (i.e., Cd, Pb, Ni, Cu, and Zn) in the feather samples were observed in the water bird species, including the Red-wattled Lapwing, Asian Openbill, and Watercock. Unlike the other groups of birds, we observed that only these water birds had higher levels of Cd, Pb, Cu, and Zn in their feathers than in their livers and kidneys, which were similar to an earlier report in other water birds: the Black-crowned Night Heron and Indian Pond Heron [50]. According to the data, these water bird species may specially store and excrete those metals through their feathers, and their feathers may be appropriate bioindicator samples for long-term exposure to the environment.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, there is no discernible difference in all the metal accumulations in the feathers among the six groups of birds, but the maximum concentrations of the heavy metals (i.e., Cd, Pb, Ni, Cu, and Zn) in the feather samples were observed in the water bird species, including the Red-wattled Lapwing, Asian Openbill, and Watercock. Unlike the other groups of birds, we observed that only these water birds had higher levels of Cd, Pb, Cu, and Zn in their feathers than in their livers and kidneys, which were similar to an earlier report in other water birds: the Black-crowned Night Heron and Indian Pond Heron [50]. According to the data, these water bird species may specially store and excrete those metals through their feathers, and their feathers may be appropriate bioindicator samples for long-term exposure to the environment.…”
Section: Discussionsupporting
confidence: 90%
“…NA not available. References list: 1, this study; 2, Durmaz et al, 2017 ; 3, Agusa et al, 2005 ; 4, Dahmardeh Behrooz & Burger, 2022 ; 5, Kojadinovic et al, 2007 ; 6, Sinkakarimi et al, 2018 ; 7, Lucia et al, 2010 ; 8, Pandiyan et al, 2022 …”
Section: Discussionmentioning
confidence: 98%
“…Similar nondestructive approaches were used to analyze certain metals in other species, such as feathers and egg shells in birds [ 1 , 12 , 17 , 18 , 19 ]. Cu, Cr, and Pb have noteworthy physiological and behavioral effects on a variety of animal species [ 26 , 27 , 28 , 29 , 30 ]. Copper, chromium, and lead were found in higher amounts in the feces of the fishing cat from the Coringa Wildlife Sanctuary than in the feces of other mammal species tested elsewhere in the globe, as determined by the present research.…”
Section: Discussionmentioning
confidence: 99%